Encounters with crack: Beginning, lenght of use, daily quantity and form of use - Suelen Cardoso Leite; Michele Mandagará de Oliveira; Vania Dias Cruz (SMAD: Revista Eletrônica Saúde Mental Álcool e Drogas, 2015)
The aim of this study was to discover trajectories of use as well as consumption patterns among those who use crack. This is a descriptive-exploratory study with a qualitative approach, conducted with 14 individuals monitored by the Reduced Harm Strategy in the city of Pelotas/RS, using a semi-structured interview. The results indicate that the majority of users’ first contact with illegal drugs was with marihuana and other forms of cocaine, before choosing crack as their drug of choice. Although crack use is compulsive, there are those who manage to control their use of substance.